2003
DOI: 10.1021/jo0341564
|View full text |Cite
|
Sign up to set email alerts
|

Deprotonation Sites of Acetohydroxamic Acid Isomers. A Theoretical and Experimental Study

Abstract: Theoretical (ab initio calculations) and experimental (NMR, spectrophotometric, and potentiometric measurements) investigations of the isomers of acetohydroxamic acid (AHA) and their deprotonation processes have been performed. Calculations with the Gaussian 98 package, refined at the MP2(FC)/AUG-cc-pVDZ level considering the molecule isolated, indicate that the Z(cis) amide is the most stable form of the neutral molecule. This species and the less stable (Z)-imide form undergo deprotonation, giving rise to tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 43 publications
0
43
0
1
Order By: Relevance
“…). [19] The two protonation processes of the GABAha anion (L À ) overlap and cannot be distinguished by potentiometry. [20] To elucidate the protonation microequilibria, GABAha was studied by conducting 1 H NMR titrations in D 2 O solution.…”
Section: Resultsmentioning
confidence: 99%
“…). [19] The two protonation processes of the GABAha anion (L À ) overlap and cannot be distinguished by potentiometry. [20] To elucidate the protonation microequilibria, GABAha was studied by conducting 1 H NMR titrations in D 2 O solution.…”
Section: Resultsmentioning
confidence: 99%
“…N-methylhydroxyurea (NMHU) and methoxyurea (MetU). The hydroxamic acids contain the smallest O=CNH unit that can bind to the DNA helix, 14,15 and the observed biological activities of hydroxamic acids might be related to the similarity between the O=CNH unit and analogous structural segments found in proteins. 16 Hence, knowledge of the favoured ionization sites is important for understanding the role played by hydroxamic acids in biological processes, but also in metal ion complexation, since these processes could be interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…The preferred deprotonation site for acid molecules in liquid water is still in dispute. Experiments applying different spectroscopic methods, chemical substituents, solvents, and in some cases, N-and O-alkylation (thus preventing deprotonation at those sites), have reached differing conclusions or have suggested that both tautomers may be present [5][6][7][8][9][10]. On the theoretical side, Hartree Fock (HF), Møller-Plesset second-order (MP2), and semi-empirical quantum methods have shown that in the gas phase, formohydroxamic acid and acetohydroxamic acid preferentially deprotonate at the N-site [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…1c). This trend holds when a dielectric continuum model [10] or a semi-empirical quantum chemistry description using a gas phase cluster with four explicit water molecules [11] is used to mimic an aqueous environment solvating the hydroxamate anion, although both treatments predict that water stabilizes the O-deprotonated cis-tautomer more than the N-deprotonated one. Density Functional Theory (DFT) with the B3LYP exchange correlation functional [12,13] yields a similar relative stability for isolated hydroxamate anions in the gas phase [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation